2017
DOI: 10.1038/nprot.2016.174
|View full text |Cite
|
Sign up to set email alerts
|

Conditional reprogramming and long-term expansion of normal and tumor cells from human biospecimens

Abstract: Historically, it has been difficult to propagate cells in vitro that are derived directly from human tumors or healthy tissue. However, in vitro preclinical models are essential tools for both the study of basic cancer biology and the promotion of translational research, including drug discovery and drug target identification. This protocol describes conditional reprogramming (CR), which involves coculture of irradiated mouse fibroblast feeder cells with normal and tumor human epithelial cells in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
350
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(375 citation statements)
references
References 53 publications
4
350
2
Order By: Relevance
“…We have previously demonstrated that adult human lung fibroblasts do not support long‐term normal airway epithelial cell expansion in the same way as 3T3‐J2 cells17 so the use of adult and/or human feeder cells might favor tumor cell expansion. Relevant biological differences might also exist between mitotic inactivation using irradiation4, 9 rather than mitomycin C, as used here. Alternatively, different tissue acquisition methods,9 feeder cell‐conditioned medium,10, 27 low oxygen,10 harsh tissue digestion protocols26 and/or initially serum‐starving cells6 might help to select tumor cells by inducing differentiation or apoptosis in normal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that adult human lung fibroblasts do not support long‐term normal airway epithelial cell expansion in the same way as 3T3‐J2 cells17 so the use of adult and/or human feeder cells might favor tumor cell expansion. Relevant biological differences might also exist between mitotic inactivation using irradiation4, 9 rather than mitomycin C, as used here. Alternatively, different tissue acquisition methods,9 feeder cell‐conditioned medium,10, 27 low oxygen,10 harsh tissue digestion protocols26 and/or initially serum‐starving cells6 might help to select tumor cells by inducing differentiation or apoptosis in normal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the primary culture of human cancer cells has been challenging, with few tumors amenable to culture on plastic, so this protocol, known as “conditional reprogramming” or “3T3 + Y,” has naturally attracted attention in the cancer community. To date, variants of this protocol have allowed cancer cell cultures to be established across multiple cancer types including lung, prostate, pancreas and colon 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…Patient-derived cell lines via CR can be rapidly established [203] and are suitable to screen large drug libraries [204, 205], or to test drug combinations to overcome acquired resistance to targeted therapy [206]. While phenotypic features and the genetic heterogeneity of the original tumor are retained in short term CR cultures, the enrichment of specific cell populations, including non-transformed epithelial cells in this model, requires cross-verification of pheno- and genotypic features of donor tissues and CR cells.…”
Section: The Use Of In Vitro and In Vivo Models For Guiding Precisionmentioning
confidence: 99%
“…CR is a cell culture technique used to rapidly and efficiently establish patient-derived cell cultures from both human normal and tumor cells [155], which is accomplished by co-culturing them with irradiated mouse fibroblast feeder cells in the presence of a Rho kinase inhibitor (Y-27632). In CR culture conditions, cells are rapidly reprogrammed to cells with the characteristics of adult stem cells.…”
Section: Current Lfs Disease Modelsmentioning
confidence: 99%